Electric Field Characteristics of Various Percentages of LLDPE-Natural Rubber Composition Under Moisture Conditions - Majunit, Mohamad Azzamuddin, Nor Akmal Mohd Jamail; Nordiana Azlin Othman; Muhammad Saufi Kamarudin; Nor Shahida Mohd Jamail (International Journal of Integrated Engineering, 2025)
Enhancing the insulation performance of high-voltage cables is critical for ensuring long-term reliability in modern power systems. One major concern is the degradation of insulation due to sustained exposure to high electric fields, which can lead to flashover events. This study focuses on the electric field behavior of Linear Low-Density Polyethylene (LLDPE) blended with Natural Rubber (NR), examined under both dry and moisture-exposed conditions. Composite samples containing 0% to 30% NR were prepared through mechanical blending and submerged in water for 70 days to evaluate moisture absorption. To support simulation work, the relative permittivity of each sample in both conditions was measured using a Keysight 16514B dielectric test fixture.These permittivity values were incorporated into a COMSOL electrostatic model with cylindrical electrodes to simulate electric field distributions. Among all tested compositions, the sample with 30% natural rubber consistently demonstrated the lowest electric field intensity, even under moist conditions. This enhanced performance is attributed to the influence of natural rubber on the dielectric properties, promoting a more uniform electric field distribution despite higher water uptake. The findings suggest that LLDPE-NR composites with higher NR content hold significant potential for improving insulation in high-voltage cable applications.